Censorship and Creativity: The Case of Sampson Perry, Radical Editor in 1790s Paris and London - Rachel Rogers (Revue LISA)
This article examines the case of Sampson Perry, a little-known but intriguing figure of the British radical movement at the end of the eighteenth century. It argues that his experience of censorship and persistent repression both in Britain and France during the 1790s, far from undermining his spirit of opposition, galvanised and radicalised it. Through a study of Perry’s exile to revolutionary France after repeated libel battles with William Pitt’s administration, his involvement in the British radical circle in the French capital and his return to Britain after a period of incarceration in French jails during the Terror, I will attempt to show that Perry responded innovatively to constraint, finding new outlets for the expression of dissent in a political context where toleration of opposition was ever-narrowing.